INVESTMENT MANAGER'S RESPONSIBILITY RELATED TO THE DEFAULT TOWARDS THE INVESTOR - Ardha, Dea Justicia (Nurani, 2021)
Mutual funds are a forum for fund owners/investors to invest their funds in securities portfolios by the Investment Manager, in other words, the investment manager has an important role in managing investors' funds. Moreover, the funds managed by the investment manager are very large, however, the regulation regarding this matter is deemed inadequate so it is not uncommon for investment managers to neglect by ignoring the rights of investors which cause investors to suffer losses and are not protected. The issues that will be discussed are how the legal protection provided to mutual fund investors and the responsibilities of investment managers who default on losses suffered by investors. Based on these issues, the purpose of this research is to find out the legal protection for mutual fund investors who suffer losses due to errors from investment managers. This research uses an empirical legal research method by using the data collection techniques through interviews. From the data obtained, it shows a form of protection that given provided to investors is in the form of opened information. The investment manager will be responsible for the losses suffered by the investors, but is not more than the fee given by investors to the investment manager. If the investors’ report is not responded to, or Bapepam’s action against the investment manager which is proven to be inadequate for investors, then investors can file a lawsuit against the law through the district court. Investors must have sufficient evidences to prove the investment manager’s negligence which resulted in losses.